Accuracy and effectiveness of electronic pediatric early warning score (PEWS): A literature review - Dewi Natalia; Dian Ramawati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: The Pediatric Early Warning Score (PEWS) is important in assessing the risk of worsening of the condition in hospitalized pediatric patients. PEWS can be done manually and electronically. Purpose: To determine the effectiveness of using electronic PEWS in inpatient pediatric patients. Method: Literature study using the PRISMA diagram approach. Search for articles using the PICO formula in the Pubmed, Science Direct, Google Scholar, Sage Journal and Scopus databases for 2017-2023 with the keywords